Nonlinear features of the transition of a liquid crystalline mixture into an isotropic state under the action of alcohol vapors - Z. Mykytyuk; H. Barylo; I. Kremer; Y. Kachurak; O. Samoilov; I. Kogut (Фізика і хімія твердого тіла, 2023)
The work of an optical sensor for determining the concentration of alcohols, in particular methanol, ethanol and isopropanol, based on a liquid crystal sensitive element, was studied. The sensitive element is a mixture of cholesteric liquid crystal CB15 and nematic impurity E7. The detection and reaction of the sensitive element to the presence of alcohol vapors is investigated.